2022
DOI: 10.1371/journal.pone.0262883
|View full text |Cite
|
Sign up to set email alerts
|

Weighted assignment fusion algorithm of evidence conflict based on Euclidean distance and weighting strategy, and application in the wind turbine system

Abstract: In the process of intelligent system operation fault diagnosis and decision making, the multi-source, heterogeneous, complex, and fuzzy characteristics of information make the conflict, uncertainty, and validity problems appear in the process of information fusion, which has not been solved. In this study, we analyze the credibility and variation of conflict among evidence from the perspective of conflict credibility weight and propose an improved model of multi-source information fusion based on Dempster-Shaf… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(6 citation statements)
references
References 51 publications
0
6
0
Order By: Relevance
“…This level includes machine learning (ML), platforms, and application technologies (computer vision (CV), speech recognition (SR), natural language processing (NLP)). Also, recent years have witnessed China's extensive research and development efforts of vertical technologies, resulting in mature technologies and obvious competitive advantages CV and SR. On the other hand, IFT can collect and integrate various information sources, multimedia, and multiformat information to generate a complete, accurate, timely, effective, and comprehensive information process [ 22 , 23 ]. Figure 2 gives the working principle of a multisource information fusion system (IFS).…”
Section: Methodsmentioning
confidence: 99%
“…This level includes machine learning (ML), platforms, and application technologies (computer vision (CV), speech recognition (SR), natural language processing (NLP)). Also, recent years have witnessed China's extensive research and development efforts of vertical technologies, resulting in mature technologies and obvious competitive advantages CV and SR. On the other hand, IFT can collect and integrate various information sources, multimedia, and multiformat information to generate a complete, accurate, timely, effective, and comprehensive information process [ 22 , 23 ]. Figure 2 gives the working principle of a multisource information fusion system (IFS).…”
Section: Methodsmentioning
confidence: 99%
“…To further validate the robustness and reliability of the model, random error data were added to the original data to The improved MADS algorithm is tested now, and the results showed that the diagnosis results of the evidence fusion theory algorithm proposed in this work had a higher accuracy rate of 99.80% compared with the diagnosis results of a single vibration signal; the measured height conflict rate was 0.91%, When there is a high degree of conflict, this model handles highly conflicting data better, and the algorithm can throw an exception while giving the diagnosis result to prevent misjudgment; when there is no high degree of conflict, the accuracy rate is as high as 99.91%, which proves the effectiveness of the evidence fusion algorithm. Even if the random error rate reaches 15% during the robustness test, the classification accuracy [39] 0.5218 0.7934 0.8328 Gou et al [40] 0.5597 0.6048 0.8744 Our MADS 0.8698 0.9775 0.9932 DS S({F 6 }) 0.3245 0.5424 0.5582 Ghosh et al [28] 0.4524 0.8257 0.8553 Ma et al [39] 0.5177 0.7729 0.7418 Gou et al [40] 0.5269 0.5967 0.8523 Our MADS 0.8378 0.9675 0.9835 DS S({F 9 }) 0.3048 0.5298 0.5582 Ghosh et al [28] 0.4496 0.8037 0.8553 Ma et al [39] 0.5165 0.7579 0.7418 Gou et al [40] 0.5129 0.5563 0.8523 Our MADS 0.8251 0.9543 0.9749 remains over 95%. The findings of the confusion matrix test demonstrate that the UVTM technique can successfully exclude samples from uncertain categories and enhance the model's capacity to discriminate diagnostic results with low confidence.…”
Section: Evidence Fusion Casesmentioning
confidence: 99%
“…By collecting the tags of users' historical participation activities and the personalized tags filled by users themselves, we learn to calculate users' preferred interests, and based on this, we calculate the similarity between users and each item in the set of items to be recommended, and then sort and recommend them to the users according to the similarity calculation results. Since the data of this system are mainly low-dimensional data and need more accurate results, we compare several distance calculation formulas and finally use Euclidean Metric to calculate the similarity, which has the advantages of easy understanding and simple calculation, and the formula for calculating the distance between two points in n-dimensional space is shown in equation (1) [10][11][12] .…”
Section: Recommendation Algorithmmentioning
confidence: 99%